Carotid artery direct access for mechanical thrombectomy: the Carotid Artery Puncture Evaluation (CARE) study. (16th December 2021) - Dumas, Victor; Kaesmacher, Johannes; Ognard, Julien; Forestier, Géraud; Dargazanli, Cyril; Janot, Kevin; Behme, Daniel; Shotar, Eimad; Chabert, Emmanuel; Velasco, Stéphane; Bricout, Nicolas; Ben Hassen, Wagih; et al.
Abstract : Background: In acute ischemic stroke due to anterior large vessel occlusion (AIS-LVO), accessing the target occluded vessel for mechanical thrombectomy (MT) is sometimes impossible through the femoral approach. We aimed to evaluate the safety and efficacy of direct carotid artery puncture (DCP) for MT in patients with failed alternative vascular access. Methods: We retrospectively analyzed data from 45 stroke centers in France, Switzerland and Germany through two research networks from January 2015 to July 2019. We collected physician-centered data on DCP practices and baseline characteristics, procedural variables and clinical outcome after DCP. Uni- and multivariable models were conducted to assess risk factors for complications. Results: From January 2015 to July 2019, 28 149 MT were performed, of which 108 (0.39%) resulted in DCP due to unsuccessful vascular access. After DCP, 77 patients (71.3%) had successful reperfusion (modified Thrombolysis In Cerebral Infarction (mTICI) score ≥2b) and 28 (25.9%) were independent (modified Rankin Scale (mRS) score 0–2) at 3 months. 20 complications (18.5%) attributed to DCP occurred, all of them during or within 1 hour of the procedure. Complications led to extension of the intubation time in the intensive care unit in 7 patients (6.4%) and resulted in death in 3 (2.8%). The absence of use of a hemostatic closure device was associated with a higher complication risk (OR 3.04, 95% CI 1.03 to 8.97; p=0043). Conclusion: In this large multicentric study, DCP was scantly performed for vascular access to perform MT (0.39%) in patients with AIS-LVO and had a high rate of complications (18.5%). Our results provide arguments for not closing the cervical access by manual compression after MT.